Akceptacja choroby w grupie pacjentów z rozpoznaną dusznicą bolesną niestabilną = Acceptance of the disease in patients with a diagnosis of unstable angina - Łuczyk, Robert; Juśko, Aneta; Łuczyk, Marta; Krzyżanowska, Ewa; Plottke, Agnieszka (Journal of Education, Health and Sport, 2016)
Łuczyk Robert, Juśko Aneta, Łuczyk Marta, Krzyżanowska Ewa, Plottke Agnieszka. Akceptacja choroby w grupie pacjentów z rozpoznaną dusznicą bolesną niestabilną = Acceptance of the disease in patients with a diagnosis of unstable angina. Journal of Education, Health and Sport. 2016;6(7):453-470. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.58612 http://ojs.ukw.edu.pl/index.php/johs/article/view/3709 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.06.2016. Revised 09.07.2016. Accepted: 25.07.2016. Akceptacja choroby w grupie pacjentów z rozpoznaną dusznicą bolesną niestabilną Acceptance of the disease in patients with a diagnosis of unstable angina Robert Łuczyk1, Aneta Juśko3, Marta Łuczyk2, Ewa Krzyżanowska1, Agnieszka Plottke 1Katedra Interny z Zakładem Pielęgniarstwa Internistycznego, Wydział Nauk o Zdrowiu Uniwersytetu Medycznego w Lublinie 1Department of Internal Medicine with the Department of Internal Nursing, Faculty of Health Sciences, Medical University of Lublin 2Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Wydział Nauk o Zdrowiu Uniwersytetu Medycznego w Lublinie 2Department of Oncology and Environmental Health, Faculty of Health Sciences, Medical University of Lublin 3Absolwentka Wydziału Nauk o Zdrowiu Uniwersytetu Medycznego w Lublinie 3A graduate of the Faculty of Health Sciences, Medical University of Lublin Streszczenie Wstęp. Niestabilna dusznica bolesna należąca do ostrych zespołów wieńcowych jest wynikiem zaostrzenia przebiegu choroby i stanowi zagrożenie dla życia pacjenta, ponieważ postępujące niedokrwienie mięśnia sercowego może powodować zawał serca i nagły zgon [15, 16, 17]. Zaakceptowanie choroby niesie za sobą wiele korzyści, które w rezultacie poprawiają przebieg choroby i dalsze rokowanie [18]. Celem pracy była ocena akceptacji choroby w grupie pacjentów z niestabilną dusznicą bolesną. Materiał i metoda. Badania przeprowadzono w grupie 200 osób w różnym wieku, różnej płci, niezależnie od miejsca zamieszkania i poziomu wykształcenia z rozpoznaną niestabilną dusznicą bolesną. W badaniach wykorzystano Skalę Akceptacji Choroby (ang. Acceptance of Illness Scale, AIS) – która służy do oceny stopnia akceptacji wśród osób dorosłych i aktualnie chorych. Wyniki badań. 1. Wśród pacjentów z niestabilną dusznicą bolesną występuje średni poziom akceptacji choroby. 2. Wraz z wiekiem zmniejsza się poziom akceptacji choroby. 3. Stwierdzono, iż osoby z wyższym wykształceniem wykazują wyższy poziom akceptacji choroby. 4. Pacjenci aktywni zawodowo mają wyższy poziom akceptacji choroby, niż osoby bezrobotne, bądź przebywające na rencie lub emeryturze. 5. Osoby, które są w związku małżeńskim bardziej akceptują chorobę w porównaniu do osób owdowiałych czy będących w stanie wolnym. 6. Dłuższy czas trwania choroby wpływa na obniżenie poziomu akceptacji choroby. 7. Częstsze hospitalizacje pacjentów z niestabilną dusznicą bolesną wpływają na obniżenie poziomu akceptacji choroby. Summary Admission. Unstable angina belongs to the acute coronary syndrome is the result of an exacerbation of the disease and a threat to the life of the patient, because the progressive myocardial ischemia can cause heart attacks and sudden death [15, 16, 17]. Accepting the disease brings a lot of benefits that result in improved disease prognosis and further [18]. The aim of this study was to assess the acceptability of the disease in patients with unstable angina. Material and methods. The study was conducted among 200 people of different ages, different sexes, irrespective of the place of residence and level of education with a diagnosis of unstable angina. The study used Acceptance of Illness Scale (Eng. Acceptance of Illness Scale, AIS) - which is used to assess the degree of acceptance among adults and currently sick. Findings. 1. Among patients with unstable angina is the average level of acceptance of the disease. 2. With age decreases the level of acceptance of the disease. 3. It was found that people with higher education show a higher level of acceptance of the disease. 4. Patients economically active have a higher level of acceptance of the disease than those who are unemployed or staying retired or retired. 5. Persons who are married more accepting of the disease compared to those who are widowed or unmarried. 6. The longer duration of the disease, lowers the level of acceptance of the disease. 7. More frequent hospitalizations of patients with unstable angina impact on reducing the level of acceptance of the disease. Słowa kluczowe: akceptacja choroby, choroba niedokrwienna mięśnia sercowego, angina pectoris non stabilisata, dusznica bolesna niestabilna. Keywords: acceptance of the disease, ischemic myocardial infarction, unstable angina.